DAPUR KE PANGGUNG: BENTUK DAN MODA PERTUNJUKAN TALEMPONG GANDANG LASUANG - Tri Ananda; Wiwik Sushartami; Aton Rustandi Mulyana (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2023)
Talempong Gandang Lasuang Talempong Gandang Lasuang is one of the Minangkabau women's talempong music ensembles in Sikapak Timur Village, Pariaman City. This art had disappeared in Sikapak in the 1980s and reappeared in 2010 with a different performance space, from the kitchen to the stages of the performing arts realm followed by changes in its formal elements. This study aims to determine changes in the form and mode of TGL performances in the kitchen and on stage. This research is a qualitative research. The results of this study show that, TGL kitchen and stage are performance events with different forms and modes of performance.  As a talempong music ensemble, the change of TGL from the kitchen to the stage is related to six basic elements of music namely transition, style, genre, text, movement and composition. The formal elements are presented in two modes of performance according to the space; kitchen and participatory mode which contains the idea of play; stage and presentational mode which contains the idea of display.